2015
DOI: 10.1016/j.molcel.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Yearly Planning Meetings: Individualized Development Plans Aren’t Just More Paperwork

Abstract: The National Institutes of Health (NIH) encourages trainees to make Individualized Development Plans to help them prepare for academic and nonacademic careers. We describe our approach to building an Individualized Development Plan, the reasons we find them useful and empowering for both PIs and trainees, and resources to help other labs implement them constructively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…Goal setting is recognized as a critical step in achieving one's objectives in the work environment [19] and increasingly expected in the academic environment [9,[20][21][22]. The use of IDPs as a formal tool to communicate career objectives between mentors and mentees is also increasing in academic settings [23], particularly with the National Institutes of Health 2014 [24] policy requiring IDPs for funded trainees.…”
Section: Initiative Ii: Career Development Planning Organized By the Mamentioning
confidence: 99%
“…Goal setting is recognized as a critical step in achieving one's objectives in the work environment [19] and increasingly expected in the academic environment [9,[20][21][22]. The use of IDPs as a formal tool to communicate career objectives between mentors and mentees is also increasing in academic settings [23], particularly with the National Institutes of Health 2014 [24] policy requiring IDPs for funded trainees.…”
Section: Initiative Ii: Career Development Planning Organized By the Mamentioning
confidence: 99%
“…These are critical factors in being able to effectively engage in and benefit from robust mentoring relationships. Some tools have emerged which are intended to facilitate strategic self-assessment, including versions of an individual development plan (IDP; Clifford, 2002;Vincent et al, 2015). The use of IDPs in particular has been supported as critical for promoting structured bilateral conversations between mentors and mentees (Faber, 2015;Vincent et al, 2015).…”
Section: Self-reflectionmentioning
confidence: 99%
“…Also in 2014, a survey of over 200 postdoctoral researchers found that 19% of respondents used the IDP with 71% of those users finding it valuable 4 . The IDP has been suggested to be capable of, for example, enhancing the structure of a training environment, facilitating better communication between mentees and mentors, aiding in identifying and pursuing career paths, guiding the identification of skills and knowledge gaps and creating action plans for addressing such gaps 4 , 8 10 . IDPs are suggested to be a staple career development activity for PhD trainees, especially related to supporting trainees’ preparation for and decisions in navigating a diverse job market 11 .…”
Section: Introductionmentioning
confidence: 99%